Modernity and Metropolis - Brooker, P. author. aut Link
IX, 230 p.
Keywords: A study of urban identity and community looks at selected twentieth century literary and film texts in the context of theorizations of modernism, postmodernism, postcoloniality and globalization. Brooker draws on Beck and Giddens to propose a 'reflexive modernism' which rewrites and re-imagines the urban scene. The principal cities considered are London and New York, Tokyo, Hong Kong and Bangkok. Writers considered include Ezra Pound and T.S. Eliot, Langston Hughes, Hanif Kureishi, Iain Sinclair, Paul Auster, Sarah Schulman and William Gibson. Filmmakers include Patrick Keiller and Wong Kar-Wai.